Charging Reactions Promoted by Geometrically Necessary Dislocations in Battery Materials Revealed by In Situ Single‐Particle Synchrotron Measurements. Issue 37 (6th August 2020) - Xu, Zhengrui; Hou, Dong; Kautz, David J.; Liu, Wenjun; Xu, Ruqing; Xiao, Xianghui; Lin, Feng
Abstract: Crystallographic defects exist in many redox active energy materials, e.g., battery and catalyst materials, which significantly alter their chemical properties for energy storage and conversion. However, there is lack of quantitative understanding of the interrelationship between crystallographic defects and redox reactions. Herein, crystallographic defects, such as geometrically necessary dislocations, are reported to influence the redox reactions in battery particles through single‐particle, multimodal, and in situ synchrotron measurements. Through Laue X‐ray microdiffraction, many crystallographic defects are spatially identified and statistically quantified from a large quantity of diffraction patterns in many layered oxide particles, including geometrically necessary dislocations, tilt boundaries, and mixed defects. The in situ and ex situ measurements, combining microdiffraction and X‐ray spectroscopy imaging, reveal that LiCoO2 particles with a higher concentration of geometrically necessary dislocations provide deeper charging reactions, indicating that dislocations may facilitate redox reactions in layered oxides during initial charging. The present study illustrates that a precise control of crystallographic defects and their distribution can potentially promote and homogenize redox reactions in battery materials. Abstract : Crystallographic defects are spatially identified and statistically quantified from over 10 000 Laue X‐ray microdiffraction patterns in many layered oxide particles. The single‐particle, multimodal synchrotron measurements reveal that particles with a higher concentration of geometrically necessary dislocations provide deeper charging reactions, indicating that dislocations may facilitate redox reactions in layered oxides.